Monetary integration beyond theory: Euro area practical achievements - Adina Criste (Financial Studies, 2018)
Concerns about the monetary integration issue have lasted for over five decades, outlining several criteria which embody the theory of optimum currency areas. Although the European monetary integration pattern is not based on this theory, it often serves as a reference in assessing the opportunity of adopting the euro for the candidate countries. Based on the optimum currency area criteria, the paper focuses on the euro area experience, and identifies some specific features for this currency area. These particularities are both in terms of theoretical criteria and in terms of recent challenges at the European level, challenges that require a viable reform for euro area in the near future.
Keywords: F15; F45; 330; optimum currency area; economic convergence; political decisions